Decision Support System For Training Provider Selection Using Profile Matching Method : (Case Study: Pcu (Pertamina Corporate University) - Zaki, Ahmad; Fauzana, Rahmi (Digital Zone: Jurnal Teknologi Informasi dan Komunikasi, 2024)
The process of selecting training providers at PCU (Pertamina Corporate University) is currently not very effective and efficient, still relying on conventional methods that take a long time to choose a training provider, requiring one month for each training session. Conventional document collection by applicants can lead to the loss of documents, and there is no method in the selection of training providers, resulting in frequent occurrences of sole providers and difficulties in choosing providers for specific training needs. The research has led to the development of a web-based system using the Profile Matching method. The Profile Matching method was chosen because it involves determining competency values (standard assessment criteria) required for specific types of training, serving as a reference to evaluate selected provider candidates. This method selects the best alternative from various options by comparing the individual competencies of providers with the desired training profile values, resulting in competency differences (Gains Across Product). The smaller the GAP, the higher the weight of the score generated. Providers with the highest score have the highest ranking and a greater chance of being selected as training instructors at PCU. Data collection techniques used include observation and interviews.